Distribution and clinicopathological characteristics of G-CSF expression in tumor cells and stromal cells in upper tract urothelial carcinoma - Go Kobayashi; Yohei Sekino; Hikaru Nakahara; Kohei Kobatake; Keisuke Goto; Tetsutaro Hayashi; Kazuhiro Sentani; Nobuyuki Hinata (Journal of Cancer Research and Clinical Oncology)
Abstract Background Urothelial carcinoma (UC) is a common type of malignant disease; however, the diagnostic and prognostic markers of upper urinary tract urothelial cancer (UTUC) remain poorly understood because of its rarity. Methods To clarify the clinicopathological significance of granulocyte-colony stimulating factor (G-CSF) in UTUC, we analyzed the expression and distribution of G-CSF in 112 upper tract urothelial carcinoma (UTUC) samples with immunohistochemistry. Results In normal urothelium, G-CSF expression was weak or absent, whereas high expression of G-CSF was observed in UTUC tissues, both in tumor cells (TCs) and stromal cells (SCs). G-CSF expression in the TCs and SCs was associated with nodular/flat morphology, high grade, advanced T stage, and lymphovascular invasion in UTUC. G-CSF expression in SCs was associated with poor prognosis and was an independent prognostic factor. Public data showed that G-CSF expression was also associated with decreased progression-free survival and disease-specific survival. A prognostic model was constructed by incorporating the presence or absence of G-CSF expression along with clinicopathologic factors, which allowed for a more accurate prediction of poor prognosis. We further showed that G-CSF expression was associated with a high Ki-67 labeling index and with PD-L1, HER2, and p53 expression in UTUC. Conclusion G-CSF expression in TCs and SCs may play a crucial role in UTUC tumor progression. Notably, stromal G-CSF expression showed significant prognostic value, even when compared to major clinicopathological factors, suggesting that the evaluation of G-CSF expression may contribute to clinical decision-making in patients with UTUC.